2004
DOI: 10.1021/ma047940e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,4-Diphenyl-Substituted Poly(Thienylene Vinylene), Low-Band-Gap Polymers via the Dithiocarbamate Route

Abstract: It has been demonstrated that the dithiocarbamate precursor route is a suitable pathway towards poly(thienylene vinylene) (PTV)-type low-band-gap polymers. Two particular dithiocarbamate precursor polymers and the corresponding conjugated polymers, poly(3,4-diphenyl-2,5-thienylene vinylene) and poly(3,4-bis(4-butylphenyl)-2,5-thienylene vinylene), have been studied. The introduction of butyl side chains in the latter leads to excellent solubility in common organic solvents. Both polymers have been prepared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 21 publications
2
69
0
Order By: Relevance
“…Similar experiments were performed also for ammonia and ethanol however, the electrical conductivity of the film decreased with increasing of the NH 3 and EtOH concentrations (Figs. 2ab, 3ab).…”
Section: Electrochemical Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Similar experiments were performed also for ammonia and ethanol however, the electrical conductivity of the film decreased with increasing of the NH 3 and EtOH concentrations (Figs. 2ab, 3ab).…”
Section: Electrochemical Resultssupporting
confidence: 73%
“…However, such a procedure results in a decrease of electrical conductivity of polymers [2]. Several applications of LB films of such polymers have been proposed, based on their electrical and/or optical properties [3]. Among the possible realistic applications, changes of electrical conductivities may be used for monitoring of the presence and concentration of active gases.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the exceptionally small electron-transfer yield in the OTV:PCBM composite compared to that observed in conjugated-polymer:C 60 composites is intriguing, in particular because the LUMO energy level in OTV lies significantly higher in energy than the LUMO energy level in PCBM (-3.2 eV [16] and -4.2 eV, respectively). One plausible explanation for this behavior is based on the Rice model [17] of charge transfer in semiconducting polymers, where the p-and p*-bands form a continuum of energy levels.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 Poly(thienylenevinylene) (PTV) and its selenium analogue poly(selenylenevinylene) (PSV), the simplest vinylene based polymers, were developed later. 8,9 PTV showed improved electrical performances. 10−13 Moreover, recent findings have demonstrated that this material can exhibit singlet fission foreshowing bright prospects for photovoltaic applications because it improves power conversion efficiencies.…”
Section: Introductionmentioning
confidence: 97%